“We have tiny purses in our vaginas!!! #thanksforthat”: absurdity as a feminist method of intervention - Sundén Jenny; Paasonen Susanna (United Kingdom, 2022)
Purpose
According to thesaurus definitions, the absurd translates as “ridiculously unreasonable, unsound, or incongruous”; “extremely silly; not logical and sensible”. As further indicated in the Latin root absurdus, “out of tune, uncouth, inappropriate, ridiculous,” humor in absurd registers plays with that which is out of harmony with both reason and decency. In this article, the authors make an argument for the absurd as a feminist method for tackling heterosexism.
Design/methodology/approach
By focusing on the Twitter account “Men Write Women” (est. 2019), the rationale of which is to share literary excerpts from male authors describing women's experiences, thoughts and appearances, and which regularly broadens into social theater in the user reactions, the study explores the critical value of absurdity in feminist social media tactics.
Findings
The study proposes the absurd as a means of not merely turning things around, or inside out, but disrupting and eschewing the hegemonic logic on offer. While both absurd humor and feminist activism may begin from a site of reactivity and negative evaluation, it need not remain confined to it. Rather, by turning things preposterous, ludicrous and inappropriate, absurd laughter ends up somewhere different. The feminist value of absurd humor has to do with both its critical edge and with the affective lifts and spaces of ambiguity that it allows for.
Originality/value
Research on digital feminist activism has largely focused on the affective dynamics of anger. As there are multiple affective responses to sexism, our article foregrounds laughter and ambivalence as a means of claiming space differently in online cultures rife with hate, sexism and misogyny.